Virulence genes and resistance to antibiotics of beta-hemolytic streptococci isolated from children in Chiapas, Mexico - Javier Gutiérrez-Jiménez; Mónica Ivonne Mendoza-Orozco; Alejandra Vicente-Serrano; Lorena Mercedes Luna-Cazáres; José Manuel Feliciano-Guzmán; Jose Antonio Girón-Hernández; Jorge Eugenio Vidal (Journal of Infection in Developing Countries)
Introduction: Among beta-hemolytic streptococci, Streptococcus pyogenes causes a wide variety of human disease including pharyngitis, necrotizing fasciitis and streptococcal toxic syndrome. Group A Streptococcus (GAS) uses a variety of virulence traits to colonize and then cause damage to the host; others species of beta-hemolytic streptococci are considered as emerging pathogens for humans. Despite its recognized virulence, only few studies have investigated virulence factors of GAS strains isolated in Mexico.